Tourism and development in Sub-Saharan Africa : Current issues and local realities - Novelli, Marina (Contemporary geographies of leisure, tourism, and mobility, 2016)
"Over the past 20 years, the perception of tourism as an effective contributor to socio-economic development in the developing world has propagated, with many viewing tourism as a provider for poverty alleviation and towards other UN Millennium Development Goals. Over the same period, readers have become familiar with the paradoxes, complexities and inequalities of tourism in relation to development, wealth creation, growth, redistribution, governance and 'hosts-guests' relationships. This volume further extends this critical debate with a much-needed cohesive publication on Sub-Sahara Africa (SSA). In an era of fluctuating tourist arrivals at global level, the growth of tourism in SSA requires deeper consideration in terms of its inconsistent and questionable implications at local level. Taking as a central theme the debate on whether tourism should be used in development efforts, this book examines the way in which tourism has controversially become the way forward to development in several SSA locations and assesses bottlenecks to sustainable development as well as dilemmas and challenges faced by those SSA destinations seeking to achieve development through tourism. It offers an explicit set of chapters adopting a multi-disciplinary approach, drawing upon tourism studies, human geography, sociology, anthropology, political economy, development and environmental studies, and integrates case studies authored by local African practitioners and academics to produce a book that gave voice to local experts on local realities. Combining an overview of key theories, concepts, contemporary issues and debates as well as practical insights from a wide range of regions in SSA, this book will be a valuable resource for those investigating the role of tourism in development"--